PENGARUH TEKNIK ATTENDING KONSELOR DAN PERILAKU ASERTIF KONSELI TERHADAP KEBERHASILAN KONSELING - Mudjijanti, Fransisca; Guistiani, Gaudensia Wahyu (Educatio Vitae, 2017)
This study aims to analyze the extroverted attending technique counselors and asertiveness counselee influence on the success of counseling. The population in this study were all students of SMA Negeri 1 Dolopo Madiun who received individual counseling services among September 2015-May 2016 the number of 98 students. The sampling technique used by the author is saturated sampling thus the number of samples in the study of population of 98 students. The results processing questionnaires shaped scale is a scale of the attending technique counselors, scale of asertiveness counselee, and scale of success of the counseling. In this study, the authors propose three hypotheses, namely: 1) The first minor hypothesis that reads: attending technique counselors a significant effect the success of counseling, 2) minor second hypothesis, which reads: asertiveness counselee a significant effect the success of counseling, 3) major hypothesis reads: attending technique counselors and asertiveness counselee a significant effect the success of counseling. Data were analyzed using multiple linear regression techniques. Model regression equation Y = 19.904 + 0.208 + 0.413 subsequent analysis results show that: 1) attending technique counselors a significant effect the success of counseling, proved t hit = 3.044 > t table = 1.990, 2) asertiveness counselee a significant effect the success of counseling, proved t hit = 6.562 > t table = 1.990, 3) behavioral counselors attending and asertiveness counselee a significant effect the success of counseling, proved a F hit = 126.670 > F table = 3,515. Based on these results can be summarized as follows: 1) The first minor hypothesis is accepted. 2) The second minor hypothesis is accepted. 3) The major hypothesis is accepted.